Idiopathic subglottic stenosis in a patient with generalized port-wine stain (PWS): A case report and review of literature: - Azizian, Zahra; Behrangi, Elham; Yousefian, Laya; Moodi, Aliakbar (Galen Medical Journal, 2015)
Background: Subglottic stenosis is defined as inflammatory narrowing of the airway. It can be related to trauma, intubation, autoimmune disorders, vascular malformations, infection and congenital abnormalities. Pot-Wine Stain (PWS) is a small dermis venous malformation which is present at birth. PWS is found on face and neck, but can occur in throat and can cause subglottic stenosis. Case Report: Authors describe an 18-year-old girl with progressive dyspnea misdiagnosed with asthma having no response to medication. She has no histories of trauma, intubation, gastro-esophageal reflux disease (GERD) or allergy symptoms. Conclusion: Evaluations revealed subglottic stenosis in association with generalized PWS. To the best of our knowledge, this finding has not been reported in English medical literature. [GMJ.2015;4(2):126-28]